Context-Based Information Retrieval of Athletic Sport Management System (ASMS) - Abdullah, Muhammad Haziq Lim; Mustafa, Nuridawati; Mohammed, Norazlin; Zainon, Nur Filzah (2008)
Athletic Sport Management System (ASMS) is an online system that help user in managing and handling data for athletic sport event. This system consists of 7 main modules such as registration, lane determination, result representation etc. that will be discussed in this paper. As overall, this paper delivers the design and implementation of ASM. This study intends to develop a computerized system for athletic sport management (ASMs) that could assist administration in planning and managing the athletic sport activity. This paper presents the design and the implementation phase of the research. Context-based information retrieval is being chosen as the searching technique. to enhance the searching capability. Furthermore, we proposed the use of similar word detection and knowledge based in searching module to enhance the retrieval effectiveness.